2022
DOI: 10.1186/s41077-022-00201-8
|View full text |Cite
|
Sign up to set email alerts
|

Taking simulation out of its “safe container”—exploring the bidirectional impacts of psychological safety and simulation in an emergency department

Abstract: Background Simulation facilitators strive to ensure the psychological safety of participants during simulation events; however, we have limited understanding of how antecedent levels of psychological safety impact the simulation experience or how the simulation experience impacts real-world psychological safety. Methods We explored the experience of participants in an embedded, interprofessional simulation program at a large tertiary emergency depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Given the increasing demand for these courses internationally, faculty are often inexperienced in debriefing with consequent risk of heterogeneity of learning outcomes or even psychological harm. 24. , 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the increasing demand for these courses internationally, faculty are often inexperienced in debriefing with consequent risk of heterogeneity of learning outcomes or even psychological harm. 24. , 25.…”
Section: Discussionmentioning
confidence: 99%
“…The approach to debriefing should include establishing rapport and using a frank but non-threatening discussion of events, to ensure psychological safety of participants. 24 Psychological safety is the shared belief held by members of a team that the team is safe for interpersonal risk taking, which aims to empower individuals to perform during a simulation and engage in the debrief. 25 It is important for learners to be prompted to self-reflect on the simulation events, which should be conducted systematically.…”
Section: Discussionmentioning
confidence: 99%
“…This 'leak' of the clinician identity into the simulation space is not a new concept. Our research [64] team has previously demonstrated that participants' clinical roles and prior team interactions 'leak' into the simulation space, impacting the way that they engage with simulation. WD's reflection shows that this is also true for facilitators.…”
Section: Wearing Hats and Blending Boundariesmentioning
confidence: 99%
“…Recent work has highlighted the porous nature of the 'safe container' in simulation and the bidirectional impact of PS (or lack thereof) between simulation and clinical settings. 9 Whereas simulation educators typically have the skills, motivation and time to manage PS, clinical workplaces usually focus far less on supporting PS. As an example, bullying, which includes belittling and harsh criticism, has been shown to impact nearly half of all post-graduate medical trainees in the United States.…”
mentioning
confidence: 99%
“…Educators continue to debate what a ‘safe container’ means in challenging simulation activities and post‐simulation debriefings. Recent work has highlighted the porous nature of the ‘safe container’ in simulation and the bidirectional impact of PS (or lack thereof) between simulation and clinical settings 9 . Whereas simulation educators typically have the skills, motivation and time to manage PS, clinical workplaces usually focus far less on supporting PS.…”
mentioning
confidence: 99%